2023
DOI: 10.1049/elp2.12385
|View full text |Cite
|
Sign up to set email alerts
|

A 2D hybrid analytical electromagnetic model of the dual‐stator axial‐field flux‐switching permanent magnet motor

Fariba Farrokh,
Abolfazl Vahedi,
Hossein Torkaman
et al.

Abstract: The two‐dimensional (2D) analytical model for the calculation of the components of the flux density distribution in the air gap in a dual‐stator axial‐field flux‐switching permanent magnet (PM) motor (DSAFFSPM) is presented. The novelties of this study are deriving a 2D hybrid analytical model and replacing the rotor teeth with some surface currents for the calculation of air‐gap magnetic flux density for the first time in the DSAFFSPM motor. The 2D analytical model for DSAFFSPMs is more challenging due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The armature winding electrical loading of the harmonic with ν -pole-pair is expressed in (7), in which m is the phase number, ph N is the phase turn number, k ων is the winding factor of ν th order, and max I is the maximum armature current value.…”
Section: B Initial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The armature winding electrical loading of the harmonic with ν -pole-pair is expressed in (7), in which m is the phase number, ph N is the phase turn number, k ων is the winding factor of ν th order, and max I is the maximum armature current value.…”
Section: B Initial Designmentioning
confidence: 99%
“…or PMs [7,8]. In the conventional topologies of FSPM machines, both the armature windings and the excitation system are located on the stator structure, and significant amounts of PMs are usually used in their structure [9,10].…”
mentioning
confidence: 99%
“…Different types of technology machines include axial and radial flux machines. Studies showed that axial flux machines (AFPM) have higher torque and power density (1)(2)(3), as well as efficiency (4-6). Axial field fluxswitching machines (AFFSPM) have limited torque density due to the location of PMs and coils, but still have higher torque and efficiency than radial flux machines and can reduce costs.…”
Section: Introductionmentioning
confidence: 99%